Emergency radiology : imaging of acute pathologies - Singh, Ajay (Springer New York, 2013)
In the emergency and trauma setting, accurate and consistent interpretation of imaging studies are critical to the care of acutely ill and injured patients. Emergency radiology: imaging of acute pathologies is a comprehensive review of radiological diagnoses commonly encountered in the emergency room by radiologists, residents, and fellows.  The book is organized by anatomical sections that present the primary ER imaging areas of the acute abdomen, pelvis, thorax, neck, head, brain and spine, and osseous structures.  For each section, the common diagnoses are concisely described and are accompanied by relevant clinical facts and key teaching points that emphasize the importance of radiological interpretation in clinical patient management.  The role of modalities such as plain radiography, CT, ultrasound, MR, and nuclear medicine imaging in managing emergency conditions is highlighted.